2021
DOI: 10.3390/plants10020277
|View full text |Cite
|
Sign up to set email alerts
|

Two Advanced Cryogenic Procedures for Improving Stevia rebaudiana (Bertoni) Cryopreservation

Abstract: Cryopreservation is a useful tool for the long-term storage of plant genetic resources, and different cryogenic procedures have recently been developed. The present study focused on the use of the Droplet-vitrification (DV) and V cryo-plate protocol for the cryopreservation of Stevia rebaudiana in vitro-derived apical shoot tips and axillary shoot tips. A preliminary test showed that 90 and 120 min PVS2 (Plant Vitrification Solution 2) treatment significantly reduced the regrowth of the explants before immersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In the case of the present study, shoot tip regrowth rates were higher and plantlet regeneration and growth was faster than when the vitrification procedure was used [17]. The droplet-vitrification been developed for many other plant species [7,8,12,13,14,15,16,21,22,23,24,25,26,27]. It is a practical, user-friendly technique and is now routinely applied for the cryopreservation of shoot tips of a wide range of plant species and genotypes and could be an alternative for implementing long-term storage of germplasm.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the case of the present study, shoot tip regrowth rates were higher and plantlet regeneration and growth was faster than when the vitrification procedure was used [17]. The droplet-vitrification been developed for many other plant species [7,8,12,13,14,15,16,21,22,23,24,25,26,27]. It is a practical, user-friendly technique and is now routinely applied for the cryopreservation of shoot tips of a wide range of plant species and genotypes and could be an alternative for implementing long-term storage of germplasm.…”
Section: Resultsmentioning
confidence: 98%
“…In other studies, it was reported that the best exposure times to PVS2 were 60 min for Stevia. [8], 20 min. for Rosa hybrida L. [14], 60 min for Malus domestica Borkh.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature during the incubation of plants in PVSs is important for both toxicity and dehydration. The temperature close to 0 • C for plants treated in PVS2 is crucial and had significantly lower lethality than at 22 • C [65,[141][142][143]. When the temperature is subsequently lowered, the penetrating components of PVS2 cryoprotect the cells by restricting the molecular mobility of water molecules and preventing them from nucleating ice crystals [11].…”
Section: Vitrification Solution and Cryopreservation Methodsmentioning
confidence: 99%